Design and implementation of digital controlled analog mixers for musical audio (2019)
The design of the digital control of a mixer is implemented throughout digital potentiometers controlled by an ESP32 FreeRTOS firmware, which is communicated via serial to an Android application. Also, an analog mixer is designed throughout multiple stages. Power supply: creating a standard by converting a 120AC input to four DC outputs (15V, -15V, 5V and 3.3V) with an AC noise less than a 5% of each input. Inputs and preamplification, using instrumentation amplifiers with a 3.5mm - 1Vpp AC input, having a voltage line output preamplification of 1.23Vrms. Fader/mixer, with an adder connected to all the inputs and preamplification with a THD of 0.006%, a SINAD of 100dB and a FR without almost any amplitude voltage variations for the audible spectrum. Amplification of a power amplifier TDA2030 and output of a 20W-8{omega} speaker